Bawal Exclusive Sdn Bhd / Muhammad Syafiq Shaharuddin - Shaharuddin, Muhammad Syafiq (2021)
This case study is about Bawal Exclusive Sdn Bhd. The founder of this company is pair of spouses who are Haliza Maysuri and her husband, Mohd Rosli Awang. They started this business about 22 years ago. They are selling headscarves and niqab which is design with Swarovski crystals, and also brooch made with Swarovski crystal too. The reasons why I choose this business because the founder had shown her ethical and responsibilities as an entrepreneur. I believe that the founder will use all their strength and opportunites that they have to overcome their weakness, so that their business will growth and success in industry. Bawal Exclusive Sdn Bhd is located at 72, Jalan BP 7/8, Bandar Bukit Puchong, 47120 Puchong. Warehouse address of Bawal Exclusive is at Puchong, Malaysia. They also provided online website to purchase their headscarve at www.bawalexclusive.com. Bawal Exclusive uses premium reseller to expend their business and to sell their products to the customers. Their premium reseller is from all over Malaysia which means easy for customer to purchase their product.